Correction to: Binary black hole mergers from population III stars: uncertainties from star formation and binary star properties - Santoliquido, Filippo; Mapelli, Michela; Iorio, Giuliano; Costa, Guglielmo; Glover, Simon; Hartwig, Tilman; Klessen, Ralf S.; Merli, Lorenzo (Monthly notices of the Royal Astronomical Society, 2024)
Our paper ‘Binary black hole mergers from population III stars: uncertainties from star formation and binary star properties’ was published in MNRAS, 524, p. 307-324 (2023).After publication, we found a minor bug in cosmo$\mathcal {R}$ate, the code we used to produce the results shown in Figs 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 13, 14, 15, 17, 18, B1, and B2.In the following, we list the changes with respect to the published version of the paper. All of them are minor changes: the results and conclusions presented in the published article are not significantly affected by the bug.